Pengaruh Growth Opportunity dan Profitabilitas Terhadap Nilai Perusahaan pada Perusahaan Sub Sektor Makanan dan Minuman yang Terdaftar di Bursa Efek Indonesia - Ramadhanti, Sagita; Cipta, Wayan (Vokasi : Jurnal Riset Akuntansi, 2022)
This study aims to determine the effect of growth opportunity and profitability on firm value. The research design was used is quantitative causal. The subjects of this research are Food and Beverages Sub Sector Companies listed on the Indonesia Stock Exchange and the object of research is growth opportunity, profitability, and firm value. The sampling technique used was purposive sampling as many as 18 companies. Data were collected by document recording method and analyzed by multiple linier regression analysis. The result of study show that (1) growth opportunity and profitability had a positive significant effect on firm value, (2) growth opportunity had a positive and significant effect on firm value, (3) profitability had a positive and significant effect on firm value.